2013
DOI: 10.1021/es402659t
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Modulation of Biosafe Manganese Nanoparticles on Vigna radiata: A Detailed Molecular, Biochemical, and Biophysical Study

Abstract: Manganese (Mn) is an essential element for plants which intervenes mainly in photosynthesis. In this study we establish that manganese nanoparticles (MnNP) work as a better micronutrient than commercially available manganese salt, MnSO4 (MS) at recommended doses on leguminous plant mung bean (Vigna radiata) under laboratory condition. At higher doses it does not impart toxicity to the plant unlike MS. MnNP-treated chloroplasts show greater photophosphorylation, oxygen evolution with respect to control and MS-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(120 citation statements)
references
References 52 publications
5
109
0
Order By: Relevance
“…They found similar growth patterns and Zn accumulation in plant tissues from ZnO as from ZnSO 4 , when the products were mixed in the soil, but not when seed-banded, in which case ZnSO 4 showed superior performance in terms of solubility rate. Other studies have also reported improved biomass production, seed yield, nutrient content, and/or disease control in different plants treated with Fe, Cu, Mn, and Znbased NPs, relative to their respective salt or bulk counterparts (Prasad et al 2012;Moghaddasi et al 2013;Pradhan et al 2013;Raliya and Tarafdar 2013;Burman et al 2013;Kim et al 2014;Servin et al 2015a, b). Notable among such studies are those highlighted in Fig.…”
Section: Influence Of Packaging On the Bioactivity Of Micronutrientsmentioning
confidence: 95%
See 1 more Smart Citation
“…They found similar growth patterns and Zn accumulation in plant tissues from ZnO as from ZnSO 4 , when the products were mixed in the soil, but not when seed-banded, in which case ZnSO 4 showed superior performance in terms of solubility rate. Other studies have also reported improved biomass production, seed yield, nutrient content, and/or disease control in different plants treated with Fe, Cu, Mn, and Znbased NPs, relative to their respective salt or bulk counterparts (Prasad et al 2012;Moghaddasi et al 2013;Pradhan et al 2013;Raliya and Tarafdar 2013;Burman et al 2013;Kim et al 2014;Servin et al 2015a, b). Notable among such studies are those highlighted in Fig.…”
Section: Influence Of Packaging On the Bioactivity Of Micronutrientsmentioning
confidence: 95%
“…Leveraging advanced spectroscopic and microscopic capabilities such as X-ray absorption spectroscopy (XAS), scanning/ transmission electron microscopy-energy dispersive spectroscopy (S/TEM-EDS), confocal laser scanning microscopy (CLSM), and other similar instrumentations, novel evidences are increasingly being presented of alternative uptake into plant tissues of Fe, Cu, Mn, Ni, Mo, and Zn in the form of oxides or composite particles (Aubert et al 2012;Dimkpa et al 2012bDimkpa et al , 2013aWang et al 2012a, b;Faisal et al 2013;Ghafariyan et al 2013;Pradhan et al 2013;Bandyopadhyay et al 2015). This is in contrast to the conventional uptake of micronutrients as ions, hitherto the consensus knowledge.…”
Section: Uptake Of Nanoparticulate Nutrientsmentioning
confidence: 99%
“…titanium, silicon, silver) and nanoforms of micronutrients such as Zn, Fe and Mn, have been demonstrated as being able to improve crop growth and/or content of these elements (Larue et al 2012;Wang et al 2013a, b, c;Siddique and Al-Whaibi 2014;Servin et al 2015). Often, the positive effects of nanoparticles (NPs) on crop growth occur to a greater extent than with the equivalent dose of the same mineral nutrient presented in ionic (salt) form (Alidoust and Isoda 2013;Pradhan et al 2013;Zhao et al 2013;Kim et al 2014), and when applied at the same concentration at relatively high doses, the concentration at which toxicity occurs is lower with ions than with NPs (Dimkpa et al 2012a;Pradhan et al 2013;Kim et al 2014). The enhanced beneficial effects of NPs are due likely to the fact that unlike ionic fertilisers where a significant portion of the nutrients could be lost due to the formation of phosphate and carbonate precipitates or other soil factors, exposure to NPs is potentially controlled by the sustained but low release of the functional ions from the particles which serve as reservoirs of ions (Dimkpa et al 2012b), with plant-adequate amounts then likely taken up to offset losses due to interaction of the released ions with soil factors.…”
Section: Nanotechnology In Fertilisersmentioning
confidence: 99%
“…For example, Cu presented as CuO NPs was taken up by maize and wheat in the particulate form (Wang et al 2012a, b;Dimkpa et al 2012aDimkpa et al , 2013. Similarly, the presence of Fe and Mn NPs also has been observed in plants exposed to particulate Fe oxide and Mn (Ghafariyan et al 2013;Pradhan et al 2013), as has been MgO NPs in roots when exposure was via foliar application (Wang et al 2013a, b, c). Notably, the same crop could differentially absorb different nutrient elements provided to it in particulate form through the root, as observed in wheat for CuO vs. ZnO NPs, where Cu existed in wheat shoot mainly as CuO particles and a lower amount of dissolved forms, and Zn as Znphosphate (Dimkpa et al 2012a(Dimkpa et al , 2013.…”
Section: Nanotechnology In Fertilisersmentioning
confidence: 99%
“…Case studies Pradhan et al, (2013) produced the maximum growth enhancement over that of the controls (without Mn) in root length (by 52%), shoot length (by 38%), number of rootlets (by 71%), fresh biomass (by 38%), and dry biomass (by 100%). In comparison with seedlings treated with MnSO 4 salt, these parameters were enhanced with the use of Mn-NP by 2%, 10%, 28%, 8%, and 100%, respectively.…”
Section: Deficiency Symptomsmentioning
confidence: 95%